1982
DOI: 10.1073/pnas.79.3.820
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules and microfilaments in fixed and permeabilized cells are selectively decorated by nerve growth factor.

Abstract: A specific antibody against nerve growth factor (NGF) and indirect immunofluorescence microscopy have been used to follow the in vitro binding of NGF to cells made permeable to large molecules. All cells tested, both target (sensory neurons and PCI2 cells) and nontarget (3T3, BKH 21, C6 glioma cells), revealed a decoration of cytoskeletal structures which on the basis of their form, reactivity with antibodies, and sensitivity to specific drugs may be identified as microtubules (MTs) and microfilaments (MFs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
4
2
Order By: Relevance
“…Several models regarding a role for internalized NGF have been put forth. For instance, it has been postulated, on the basis of the interaction of NGF with tubulin and actin, that NGF may bind directly to cytoskeletal elements and promote their assembly and/or stabilization (Nasi et al, 1982). However, in our studies such a localization was not manifestly evident, and if such interactions were to occur, they would appear to do so at "substoichiometric" (Nasi et al, 1982) levels.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Several models regarding a role for internalized NGF have been put forth. For instance, it has been postulated, on the basis of the interaction of NGF with tubulin and actin, that NGF may bind directly to cytoskeletal elements and promote their assembly and/or stabilization (Nasi et al, 1982). However, in our studies such a localization was not manifestly evident, and if such interactions were to occur, they would appear to do so at "substoichiometric" (Nasi et al, 1982) levels.…”
Section: Discussioncontrasting
confidence: 65%
“…In addition to this evidence, subcellular fractionation of cells that had retrogradely transported NGF indicated that 20 to 30% of the factor was present in the nuclear fraction (Stockel et al, 1976;Johnson et al, 1978). Yet another set of studies (Nasi et al, 1982) has been interpreted to suggest that internalized NGF may directly interact with several elements of the cytoskeleton.…”
mentioning
confidence: 99%
“…This may reduce the ability of tubulin to bind to the cell surface (Parness and Hor-tribution of NGFR. Previous studies described NGF associations with cytoskeletal elements following its binding to receptors on PC12 cells (Schechter and Bothwell, 1981;Nasi et al, 1982;Vale et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Coverslips were washed five times with HBSS and processed for TEM. TEM demonstrated on microtubules (MTs) and microfilaments (MFs) (Nasi et al, 1982), cytoskeletal altering agents were applied prior to immunolocalization of the NGFR, to determine the degree and nature of the NGFR associations to the underlying cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…2A, and Calissano and Kinihi, unpublished). 3T3 cells show a lower affinity binding for N C F following paraformaldehyde fixation and methanol permeabilization which may be responsible for the fluorescent staining of cytoskeletal elements by N G F [12]. C6, like PC12 cells, show cryptic NGF binding sites with an equilibrium binding constant identical to that measured on intact cells (Fig.…”
Section: Extractiori and Kinetic Characterization Of Ngf Receptorsmentioning
confidence: 99%